THE INFLUENCE OF ATTITUDE, SUBJECTIVE NORMS, AND PERCEIVED BEHAVIORAL CONTROL ON THE INTENTION TO ADOPT ISLAMIC BANKING IN SAMARINDA CITY WITH RELIGIOSITY AS A MODERATING VARIABLE - Asrida, Shinta Avrillya; Mahrus, Moh; Fadhilah, Nurul; Parlina, Tika; Aziz, Aini Febriana (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study is motivated by the significant growth of Islamic banking in Indonesia; however, the level of usage of Islamic banking services remains relatively low compared to conventional banks, including in Samarinda City. The Theory of Planned Behavior (TPB) is employed in this research to analyze the influence of attitude, subjective norms, and perceived behavioral control on the intention to adopt banking services. Additionally, religiosity, as a personal value that plays a crucial role in the financial decisions of the Muslim community, is tested as a moderating variable to strengthen the relationship between these independent variables and the dependent variable. This study aims to determine the significant and simultaneous effects of attitude, subjective norms, and perceived behavioral control on the intention to adopt Islamic banking in Samarinda City, with religiosity as a moderating variable. The research method used in this study is an associative quantitative research design, utilizing primary data obtained from direct responses to questions posed through a questionnaire to respondents. The sample in this study is determined using non-probability sampling techniques. The population of this research consists of the residents of Samarinda City aged 17-60 years. The data analysis techniques employed in this study include instrument testing, classical assumption testing, t-tests, F-tests, coefficient of determination (R²) tests, multiple linear regression analysis, and Moderated Regression Analysis (MRA)